If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15+3(5x-12)=24
We move all terms to the left:
15+3(5x-12)-(24)=0
We add all the numbers together, and all the variables
3(5x-12)-9=0
We multiply parentheses
15x-36-9=0
We add all the numbers together, and all the variables
15x-45=0
We move all terms containing x to the left, all other terms to the right
15x=45
x=45/15
x=3
| (X+7)(2x+5)=0 | | (2/x)+7x=-12 | | 12x+3/2=9 | | 4+19x-5x^2=0 | | x2+4x=7 | | (X+5)(2x+7)=0 | | |4x-6|=|10x+2| | | 5x^2-3x-18=0 | | 0=-16t*t+9t+125 | | -5/8z+2/3=19/24 | | 9+2(5w-3)=-3(2w-5)+7w | | 0.06(3y-4)=0.5(y+4) | | 1/7(x+7)=6 | | X+(x+2)=218 | | 6=d+8/5 | | 2x-3x+3=28 | | 1x^2+2x=-1 | | 3x^2+17x-2=0 | | 3(x+7)-4=5 | | T=-2n+5 | | 1/2t+8=3 | | 3-0.3x^2-16x+500=0 | | -0.6x=16 | | X-0.25x=341.25 | | X^2-20x-1200=0 | | 3x-1=4x+8x | | 4y-3+3(2y+3)=-2(y+4) | | 3/7x-15/7x+2=6-4x | | 8+6+7a=0 | | (9x-11)-(x+3)=7x-10 | | 3/7(x−5)+2=2(3−2x) | | 3(x-5)+8=5 |